Regulatory Evolution and the Strategic Landscape of Merger and Acquisition of Nepalese Banks and Financial Institutions - Dawadi, Purna Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Nepalese banking industry has experienced significant transformation in recent years, characterized by a growing number of mergers and acquisitions (M&A) among banks and financial institutions (BFIs), influenced by regulatory factors and the quest for enhanced efficiency and capital sufficiency. The Nepalese banking industry faced a phase of considerable uncertainty and operational difficulties in recent years, putting it at a crucial point necessitating decisive strategic actions. Objectives: The research offers an examination of the regulatory structure and operational processes that regulate mergers and acquisitions in Nepal. It also clarifies the idea and implementation of mergers and acquisitions, detailing their origin and the fundamental needs within the banks and financial institutions in Nepal. Ultimately, it emphasizes the available concessions and the crucial requirements that BFIs need to satisfy during a merger and acquisition in Nepal. Methods: The study utilized a descriptive and analytical framework and relies on several acts, bylaws and regulations established in Nepal to regulate and enhance merger and acquisitions of banks and financial institutions (BFIs). Conclusion: Nepal Rastra Bank (NRB) has directly or indirectly compelled banks and financial institutions for merger and acquisition. Those banks and financial institutions which are intended to upgrade their license or those which are in critical financial situations, NRB recommends such institutions to go for merger. To facilitate merger of banks and financial institutions, NRB has issued a Merger Bye-law applicable to banks and financial institutions which determines the process of merger which BFIs need to complete with NRB. It also makes provision for different concessions which participants of a merger can get. Every bank and financial institution are relentless in their endeavor to become financially strong and operationally efficient and effective. Some of the reasons behind mergers and acquisition being a part of today’s business environment is revenue enhancement, cost reduction, vertical and horizontal operational strategies, growth of the industry, need of the product and service diversification.